Modeling the cost effectiveness of injury interventions in lower and middle income countries: opportunities and challenges - Bishai, David M (BioMed Central, 2006)
BACKGROUND: This paper estimates the cost-effectiveness of five interventions that could counter injuries in lower and middle income countries(LMICs): better traffic enforcement, erecting speed bumps, promoting helmets for bicycles, promoting helmets for motorcycles, and storing kerosene in child proof containers. METHODS: We adopt an ingredients based approach to form models of what each intervention would cost in 6 world regions over a 10 year period discounted at both 3% and 6% from both the governmental and societal perspectives. Costs are expressed in local currency converted into US $2001. Each of these interventions has been assessed for effectiveness in a LMIC in limited region, these effectiveness estimates have been used to form models of disability adjusted life years (DALYs) averted for various regions, taking account of regional differences in the baseline burden of injury. RESULTS: The interventions modeled in this paper have cost effectiveness ratios ranging from US $5 to $ 556 per DALY averted depending on region. Depending on local acceptability thresholds many of them could be judged cost-effective relative to interventions that are already adopted. Enhanced enforcement of traffic regulations is the most cost-effective interventions with an average cost per DALY of $64 CONCLUSION: Injury counter measures appear to be cost-effective based on models. More evaluations of real interventions will help to strengthen the evidence basis.